Kinetics and MR-Based Monitoring of AAV9 Vector Delivery into Cerebrospinal Fluid of Nonhuman Primates - Ohno, Kousaku (Mol Ther Methods Clin Dev, 2018)
Here we evaluated the utility of MRI to monitor intrathecal infusions in nonhuman primates. Adeno-associated virus (AAV) spiked with gadoteridol, a gadolinium-based MRI contrast agent, enabled real-time visualization of infusions delivered either via cerebromedullary cistern, lumbar, cerebromedullary and lumbar, or intracerebroventricular infusion. The kinetics of vector clearance from the cerebrospinal fluid (CSF) were analyzed. Our results highlight the value of MRI in optimizing the delivery of infusate into CSF. In particular, MRI revealed differential patterns of infusate distribution depending on the route of delivery. Gadoteridol coverage analysis showed that cerebellomedullary cistern delivery was a reliable and effective route of injection, achieving broad infusate distribution in the brain and spinal cord, and was even greater when combined with lumbar injection. In contrast, intracerebroventricular injection resulted in strong cortical coverage but little spinal distribution. Lumbar injection alone led to the distribution of MRI contrast agent mainly in the spinal cord with little cortical coverage, but this delivery route was unreliable. Similarly, vector clearance analysis showed differences between different routes of delivery. Overall, our data support the value of monitoring CSF injections to dissect different patterns of gadoteridol distribution based on the route of intrathecal administration.